Transformasi dan pembentukan ilmu fikih di era sahabat: Sebuah analisis historis - Saida, Mukhammad Fahmi Ulum; Putra, Aldo Andika; Aprilia, Diva; Rahmasari, Fani (Maliki Interdisciplinary Journal, 2024)
The period of the companions of Rasulullah SAW was the initial phase in the formation of Islamic jurisprudence, where the basics of Islamic law began to be developed and applied in various contexts of life. This article aims to analyze the development of jurisprudence during the Companion era, with a focus on the process of transformation and formation. This research methodology uses a historical-analytical approach, examining primary and secondary sources related to fiqh practices that developed among the Companions. The research results show that the Companions play an important role in forming the basis of jurisprudence through ijtihad and the application of hadith. The dynamics that occurred during that period not only involved direct interpretation of revelation, but also responses to various new problems that emerged after the death of the Prophet Muhammad SAW. This study shows that Islamic jurisprudence thought during the Companions era developed evolutionarily, which then became the foundation for the formation of schools of Islamic jurisprudence in the following period..